Efficacy of Mebendazole and Praziquantel against Soil-Transmitted Helminths and Schistosoma mansoni Infections among Schoolchildren in Northwest Ethiopia. (16th July 2021) - Ejigu, Kefale; Hailu, Tadesse; Alemu, Megbaru
Abstract : Background . Soil-transmitted helminths (STHs) and Schistosoma mansoni are the main causes of morbidity among schoolchildren in the tropics. A school-based deworming program was launched to control and eliminate the infection in endemic countries including Ethiopia. Although periodic deworming is conducted in endemic areas, the prevalence of the infection is high in the country. In addition, periodic evaluation of the efficacy of the anthelminthic drug is limited. Objective . This study is aimed at checking the efficacy of mebendazole and praziquantel with the respective STHs and Schistosoma mansoni parasites. Methods . A longitudinal study was conducted from February to March 2018 among 422 schoolchildren. Stool samples were collected at baseline and at 2 and 4 weeks posttreatment and were processed using the Kato-Katz technique. Schoolchildren positive for STHs were treated with mebendazole and those positive for Schistosoma mansoni with praziquantel. After two weeks, a second round of stool was collected and examined, and then, single-dose redosing was given to each positive child. Lastly, the third stool sample was collected two weeks after the initiation of the redosing and checked for STHs and S. mansoni parasites. A close follow-up of students who were treated was done. All the data were entered and analyzed using SPSS version 20 for analysis. Descriptive statistics was used to compute the cure rate and egg reduction rate of mebendazole and praziquantel. Results . Among 422 participants, the prevalence of STHs, hookworm, Ascaris lumbricoides, and S. mansoni was 44.7%, 35.1%, 21.1%, and 13.9%, respectively. The cure rate of mebendazole against A. lumbricoides increased from 60% in the single dose to 100% in redosing after two weeks. The cure rate of mebendazole against hookworm also increased from 32.4% in the single dose to 91.0% in the redosing. The cure rate of praziquantel against S. mansoni -infected children was 91.5% in the first round and 100% in the redosing phase. There was a 98.6-100% egg reduction rate in the redosing regimen of both drugs. Conclusion . The cure and egg reduction rates of single-dose mebendazole in the treatment of hookworm and A. lumbricoides are lower at week two than at redosing, while cure and egg reduction rates of single-dose praziquantel are satisfactory to treat S. mansoni . Therefore, single-dose praziquantel to S. mansoni and redosing of single-dose mebendazole to A. lumbricoides and hookworm infections can be used for treatment purposes.